AN ANALYTICAL STUDY OF JUDICIAL CONSIDERATIONS IN THE IMPOSITION OF CRIMINAL SANCTIONS ON JUVENILE OFFENDERS OF NARCOTICS CRIMES: A CASE STUDY OF DECISION NUMBER 12/PID.SUS-ANAK/2024/PN.SAK - Achmad Ario Miftaqul Rochman; Muh. Catur Rizky; Sudjai (RADJA PUBLIKA, 2025)
The phenomenonof child involvement in narcotics crimes, whether as users, dealers, or couriers, is a very complex legal and social problem in Indonesia. Children are often exploited by narcotics distribution networks because they are considered safer from legal threats. This creates its own problems in the criminal justice system, considering that children are in the positionof perpetrators andvictims who needspecial protection. Based on these problems, this study was conducted to analyze the judge's considerations in imposing criminal sanctions on child perpetrators of narcotics crimes andto determine the results of the legal analysis of the judge's considerations in Decision Number: 12/Pid.Sus-Anak/2024/PN.Sak based on the principles of child protection and the principles of restorative justice. This study uses a normative legal research method, with the object of research in the form of Decision Number: 12/Pid.Sus-Anak/2024/PN.Sak. The approaches used in the study are the statutory approach and the case approach. The results of the study indicate that the judge's sentencing ofchildrenin Decision No. Case No. 12/Pid.Sus-Anak/2024/PN.Sak reflects an effort to balance punishment andrehabilitation. Although the judge has considered age, social background, and provided job training, child protection and restorative justice approaches have not been comprehensively implemented. Children as victims of exploitation have not received adequate psychological recovery, education, or social reintegration. Therefore, the juvenile criminal justice system needs to prioritize rehabilitation and the best interests of the child, rather than solely punishment. The judge's decision in case No. 12/Pid.Sus-Anak/2024/PN.Sak does not fully reflect the principles of child protection and restorative justice. The child only acts as a courier, is under the influenceof an adult perpetrator, and comes from an unsupportive social environment. Despite showing remorse and cooperation, the judge still sentences him to imprisonment without considering alternatives such as diversion, rehabilitation, or social rehabilitation. The legal approach taken is morerepressive and formalistic, inconsistent with the educational and restorative objectives of child punishment. Therefore, this decision shows the needto strengthen the application ofmore humaneprinciples of justice towards children in the criminal justice system.